(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
To synthesize a series of ornidazole thiosemicarbazone analogues on the basis of literature reviews of 2-Methyl-5-nitroimidazoles and thiosemicarbazones and to evaluate all the analogues in vitro for their activity against Aspergillus niger and fumigatus. Thiosemicarbazone analogues were synthesized from oxidising ornidazole with potassium dichromate and refluxing the oxidised product with substituted thiosemicarbazide using ethanol as solvent in the acidic medium overnight. All the synthesized analogues of ornidazole showed good antifungal action against fumigatus and niger except compound C-4. Unsubstituted amine analogue C-2 has shown highest percentage inhibition (96.6%, 500 μg/ml) against fumigatus while aromatic amine with or without electronegative atom analogues C-3 and C-5 has shown highest activity against Aspergillus niger which is two times than standard drug ornidazole (100%, 1000 μg/ml).